Emerging Research in Computing, Information, Communication and Applications ERCICA 2018, Volume 1 - Shetty, N. R.; Patnaik, L. M.; Nagaraj, H. C.; Hamsavath, Prasad Naik.; Nalini, N.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents selected papers from the International Conference on Emerging Research in Computing, Information, Communication and Applications, ERCICA 2018. The conference provided an interdisciplinary forum for researchers, professional engineers and scientists, educators, and technologists to discuss, debate and promote research and technology in the emerging areas of computing, information, communication and their applications. The book discusses these research areas, providing a valuable resource for researchers and practicing engineers alike.
Chapter 1: A Computational Segmentation Tool for Processing Patient Brain MRI Image Data to Automatically Extract Gray and White Matter Regions -- Chapter 2: Developing Ontology for Smart Irrigation of Vineyards -- Chapter 3: An Intensive Review of Data Replication Algorithms for Cloud Systems -- Chapter 4: integrated cryptography for internet of things using tbf approach -- Chapter 5: Data Governance on Local Storage in Offsite -- Chapter 6: Extraction of Character Personas from Novels using Dependency Trees and Pos Tags -- Chapter 7: A Multifactor Authentication Model to mitigate the Phishing Attack of e-Service Systems from Bangladesh Perspective -- Chapter 8: Study on Energy Efficient and Lifetime Enhanced Clustering Algorithm based Routing Protocols in Wireless Sensor Network -- Chapter 9: DigiPen: An Intelligent Pen using Accelerometer for Character Recognition -- Chapter 10: Multi-language Handwritten Recognition in DWT Accuracy Anlaysis -- Chapter 11: A survey on Intelligent Transportation System using Internet of Things -- Chapter 12: Organizational digital footprint for traceability, provenance approach -- Chapter 13: Organizational digital footprint for traceability, provenance approach -- Chapter 14: Movie Recommendation System -- Chapter 15: A Semi-Automated Question Paper Builder using Long Short-Term Memory Neural Networks.
Keywords: Telecommunication; Computational intelligence; Computer networks .; Communications Engineering, Networks; Computational Intelligence; Computer Communication Networks